Occupational Hepatitis B Exposure: A Peek into Indian Dental Students’ Knowledge, Opinion, and Preventive Practices - Kumar, Sandeep; Basak, Debashish; Kumar, Amit; Dasar, Pralhad; Mishra, Prashant; Kumar, Arunoday; Kumar Singh, Siddharth; Debnath, Nitai; Gupta, Anjali (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Objective. To determine the level of knowledge, opinions, and preventive practices followed by dental students against Hepatitis B. The study also explored if any correlation existed between knowledge, opinion, and preventive practices score. Materials and Methods. A cross-sectional study was conducted in a dental teaching institution. The subjects comprised 216 dental students. The study was conducted using a pretested, self-administered questionnaire. The questionnaire was prepared to assess knowledge, opinion, and preventive practices against Hepatitis B. Kruskal-Wallis and Kendall Tau test were performed. Results. The study found that only 44.4% of the students were vaccinated with Hepatitis B vaccine. 59.3% of the students reported washing their hands after contact with patient’s body fluids. 63.9% used personal protective measures like facemask, aprons, head cap, eye shields, and so forth, while treating patients. Median knowledge, opinion, and practice scores were found to be 5.00, 3.00, and 3.00, respectively. Significant correlation was obtained between knowledge and preventive practices score (r=0.385, p value <0.0001). Conclusion. Effective measures need to be taken to improve preventive practices of the students to prevent them from risk of Hepatitis transmission. Mandatory vaccination against Hepatitis B needs to be implemented.